1986
DOI: 10.1063/1.336819
|View full text |Cite
|
Sign up to set email alerts
|

Deep electron trapping center in Si-doped InGaAlP grown by molecular-beam epitaxy

Abstract: The properties of a deep electron trapping center found in Si-doped In0.51Ga0.49−xAlxP (x=0.24) grown on Si-doped GaAs(100) substrates using molecular-beam epitaxy are studied. The trapping parameters for this center are determined as follows: thermal activation energy 0.48 eV, photoionization energy 1.25 eV, and capture barrier 0.10 eV. The concentration of this center is about seven times as high as that of the shallow donor state and is found to increase with an increasing amount of Si atoms incorporated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…1͒. Similarly, no free-carrier saturation effects were observed by Nojima et al 10 in Hall measurements of silicon doped (Al 0.25 Ga 0.75 ͒ 0.52 In 0.48 P for free-carrier concentrations up to 5ϫ10 18 cm Ϫ3 , indicating that the DX level had not crossed the Fermi level in their sample with an aluminum composition of yϭ0. 25.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…1͒. Similarly, no free-carrier saturation effects were observed by Nojima et al 10 in Hall measurements of silicon doped (Al 0.25 Ga 0.75 ͒ 0.52 In 0.48 P for free-carrier concentrations up to 5ϫ10 18 cm Ϫ3 , indicating that the DX level had not crossed the Fermi level in their sample with an aluminum composition of yϭ0. 25.…”
Section: Resultsmentioning
confidence: 62%
“…We observe no saturation of the free-electron-carrier population with increasing dopant as has been reported in n-type doping of ͑GaIn͒P by other groups. [10][11][12] The freecarrier Hall data are lower than the C -V impurity carrier concentration, indicating the presence of compensating centers. The compensation ratio was determined to be N a /N d ϭ0.41.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…From the above statement, we believe that the deep levels in Te-doped AlGaInP should be the same kinds of defects as those in previous studies. [5][6][7][8][9][10] Furthermore, the previous studies has also been revealed that the concentrations of donor-related deep levels in AlGaInP are strongly related to the Al mole ratio in (Al x Ga 1Àx ) 0:5 In 0:5 P alloys. Therefore, we envisage that the deep levels in Te-doped (Al x Ga 1Àx ) 0:5 In 0:5 P (x ¼ 0:5) may also be related to the Al mole ratio in AlGaInP.…”
mentioning
confidence: 93%
“…Investigation on deep levels in (Al x Ga 1Àx ) 0:5 In 0:5 P quaternary alloys is necessary, especially in (Al x Ga 1Àx ) 0:5 In 0:5 P (x ¼ 0:5) material due to its inherent low efficiency. Deep levels in Si-, Zn-and Se-doped (Al x Ga 1Àx ) 0:5 In 0:5 P have been widely investigated, [5][6][7][8][9][10] but the information of deep levels in Te-doped (Al x Ga 1Àx ) 0:5 In 0:5 P is still very limited. 11,12) Tellurium is conventionally used as n-type dopant in the cladding layers of high-efficiency LEDs.…”
mentioning
confidence: 99%